Impact of Escherichia coli phages as an adjunct to probiotics in modifying chicken gut microbiota - Mohd Asrore, Mohd Shaufi (2017)
The regulation of antibiotic growth promoters (AGPs) for poultry production in many countries has increased the need to find an effective alternative. Probiotics are by far the most recognised alternative to AGPs, and numerous studies have highlighted their efficacy in chickens. Probiotics are live microorganisms, and they adhere to the intestinal epithelial cells to exert their beneficial effects on the host. However, this is often restricted by indigenous gut microbes that compete for adhesion sites and nutrients. Phage application, which has almost similar mechanisms to those of AGPs, has been proposed to reduce the competition of probiotics with gut microbiota. At present, there is a paucity of information on the modulation of gut microbiota by phages and their influences on probiotic efficacy in chickens. Thus, the main objective of this study was to investigate the effects of locally isolated phages on the gut microbiota, and their impact on probiotic efficacy in chickens. The gut microbiota of chickens was first studied using high-throughput next-generation sequencing (HTNGS) of 16S rRNA gene amplicons to investigate their diversity and the target bacteria for modulation. The selected bacteria were then isolated from the chicken gut, and lytic phages were screened. Four best lytic phages were selected, characterised based on their morphological, molecular and physiological properties, and prepared as phage cocktail supplementations for an in vivo chicken trial. The in vivo chicken trial was conducted to investigate the effects of dietary treatments of phage cocktail at 0.1% (1ɸ) and 0.2% (2ɸ), 0.1% PrimaLac® probiotic (P) and their combinations (1ɸP, 2ɸP) on growth performance, serum biochemistry and immunoglobulins, haematological parameters, ileal villus height and crypt depth, relative organ weights, and gut microbiota in ilea and caeca based on real-time quantitative Polymerase Chain Reaction (qPCR) and HT-NGS 16S rRNA gene amplicons of 21 and 35 d chickens. Escherichia coli was selected as the target bacterium for gut modulation by phages owing to their consistent presence in the gut. The results from the in vivo chicken trial showed that birds in the 1ɸP group had significantly (P < 0.05) better body weight (BW), body weight gain (BWG), and feed conversion ratio (FCR), higher serum total protein, lower serum triglycerides and higher ileal villus height than the control. Chickens in the 1ɸP group also had higher (P < 0.05) serum total protein, ileal villus height, and lower crypt depth than those in the probiotic group. The gut microbiota profiles revealed that 1ɸP supplementation significantly (P < 0.05) reduced E. coli population, increased (P < 0.001) short chain fatty acid (SCFAs) producers, and improved (P < 0.001) gene expressions that are related to carbohydrate and amino acid metabolisms, and nutrient uptake, based on the predicted metagenomes analysis. The results from this study showed that 0.1% E. coli phage cocktail combined with probiotics could modulate the gut microbiota and enhance growth performance in chickens. Thus, the use of phage cocktail with probiotic would be a potential alternative to AGPs for poultry production.